Mapping Biological Risks Related to Necropsy Activities: Old Concerns and Novel Issues for the Safety of Health Professionals - Paola Tomao (MDPI AG, 2021)
Nowadays only a few studies on biological and environmental risk among healthcare workers are available in literature. The present study aims to assess the health operator’s risk of contact with microorganisms during necropsy activities, to evaluate the efficiency of current protections, to identify possible new sources of contact, and to point out possible preventive measures. In addition, considering the current pandemic scenario, the risk of transmission of SARS-CoV-2 infection in the dissection room is assessed. The objectives were pursued through two distinct monitoring campaigns carried out in different periods through sampling performed both on the corpses and at the environmental level.